Narrating the Everyday Windows on Life in Central South Africa - Wojciechowska, Magdalena; Rau, Asta; Coetzee, Jan K. (UJ Press, 2019)
The chapters in this book reflect on the practice of using narratives to understand individual and social reality. They all reveal dimensions of the same concrete reality: contemporary society of Central South Africa. Except for two, all the chapters originated from research in the program The Narrative Study of Lives, situated in the Department of Sociology at the University of the Free State in Bloemfontein, South Africa. Each chapter opens a window on an aspect of everyday life in Central South Africa. Each window displays the capacity of the narrative as a methodological tool in qualitative research to open up better understandings of everyday experience. The chapters also reflect on the epistemological journey towards unwrapping and breaking open of meaning. Narratives are one of many tools available to sociologists in their quest to understand and interpret meaning. But, when it comes to deep understanding, narratives are particularly effective in opening up more intricate levels of meaning associated with emotions, feelings, and subjective experiences.